2014
DOI: 10.1073/pnas.1312436111
|View full text |Cite
|
Sign up to set email alerts
|

Elevated hepatic 11β-hydroxysteroid dehydrogenase type 1 induces insulin resistance in uremia

Abstract: Insulin resistance and associated metabolic sequelae are common in chronic kidney disease (CKD) and are positively and independently associated with increased cardiovascular mortality. However, the pathogenesis has yet to be fully elucidated. 11β-Hydroxysteroid dehydrogenase type 1 (11βHSD1) catalyzes intracellular regeneration of active glucocorticoids, promoting insulin resistance in liver and other metabolic tissues. Using two experimental rat models of CKD (subtotal nephrectomy and adenine diet) which show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…It is interesting to note the clear similarities between our data and those recently reported by Chapagain et al (3) in two mouse models of uremia. That same study also found elevations in hepatic expression of 11␤-hydroxysteroid dehydrogenase (HSD) type 1, a key enzyme for cortisol biosynthesis and reported that treatment with an inhibitor of this enzyme led to the normalization of hepatic transcription in uremic animals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is interesting to note the clear similarities between our data and those recently reported by Chapagain et al (3) in two mouse models of uremia. That same study also found elevations in hepatic expression of 11␤-hydroxysteroid dehydrogenase (HSD) type 1, a key enzyme for cortisol biosynthesis and reported that treatment with an inhibitor of this enzyme led to the normalization of hepatic transcription in uremic animals.…”
Section: Discussionsupporting
confidence: 91%
“…Although simple, our study comprises what to our knowledge is the first characterization of human hepatocytes under uremic conditions to date, and it evoked a phenotype surprisingly like that seen in the clinical setting (5,7,11,14) and in rodent models of uremia (1,3,8).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in 11β-HSD activity lead to much more pronounced shifts of cortisol-cortisone equilibrium in local tissues than in circulation, 7 renal impairment. We identified inflammation as a major determinant of GC activation by 11β-HSD and as a confounder in the correlation of GC activation with renal impairment, thereby expanding on knowledge from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,19 Elevated 11β-HSD1 activity has been implicated in metabolic disease and insulin resistance. 7,26,27 Whether elevated 11β-HSD1 activity is involved in insulin resistance in the setting of human CKD has not yet been explored. 7,26,27 Whether elevated 11β-HSD1 activity is involved in insulin resistance in the setting of human CKD has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In renal medulla, 11bHSD1 activation induced salt-sensitive hypertension, which was reversed by 11bHSD1 inhibition [134]. Recent experimental data demonstrate that, in CKD hepatic and adipose tissue, 11bHSD1 is upregulated as a result of increased oxidative stress and proinflammatory cytokines interleukin (IL)-1, TNF-/, and IL-6, and promotes NAFLD, insulin resistance, hypertension, hyperglycemia, and dyslipidemia, all reversed by the 11bHSD1 inhibitor carbenoxolone [135]. These data make 11bHSD1 inhibition an appealing strategy for managing CKD-associated metabolic disorders: accordingly, in a recent Phase I RCT, the 11bHSD1 inhibitor RO5093151 significantly improved radiological steatosis in NAFLD [136].…”
Section: Glomerular Hyperfiltration and Ras Activationmentioning
confidence: 99%